The ICT in an Unequal World. Observations on the European Union States - Carlos RAMIREZ VALDEBENITO; Elena Madalina GHERGHINA (Communications of International Proceedings, 2021)
The Industrial Revolution 4.0 impacts all areas of knowledge, technology becoming a requirement of the 21st century for the whole society. However, the processes of automation and digitalization take place uniformly neither across all economies nor at the individual level. This paper proposes to verify the existence of the correlation between internet use and inequality and between internet use and the poverty rate for the 27 member states of the European Union for the period 2010-2019. The statistically significant moderate correlations between the used variables demonstrate that the most egalitarian economies and the countries with a lower poverty rate are the countries where digital inclusion is higher.
Keywords: Industrial Revolution 4.0; Inequality; Poverty rate; Digital skill